Geographic variation in the time‐frequency characteristics of high‐frequency whistles produced by killer whales (Orcinus orca). Issue 2 (11th December 2014) - Samarra, Filipa I. P.; Deecke, Volker B.; Simonis, Anne E.; Miller, Patrick J. O.
Abstract: Investigating intraspecific variation in acoustic signals can indicate the extent of isolation and divergence between populations and adaptations to local environments. Here we analyze the variation in killer whale high‐frequency (>17 kHz) whistles recorded off Norway, Iceland, and in the North Pacific. We used a combination of methods including multivariate comparisons of spectral and temporal parameters and categorization of contours to types. Our results show that spectral and temporal characteristics of high‐frequency whistles recorded in the North Pacific show significant differences from whistles recorded in the Northeast Atlantic, being generally stereotyped, lower in frequency, and slightly longer in duration. Most high‐frequency whistles from the North Pacific were downsweeps, whereas this was one of the least common types recorded in the Northeast Atlantic. The repertoire of whistles recorded in Norway was similar to Iceland, but whistles produced in Norway had significantly lower maximum frequency and frequency range. Most methods were able to discriminate between whistles of the North Pacific and the Northeast Atlantic, but were unable to consistently distinguish whistles from Iceland and Norway. This suggests that macro‐ and microgeographic differences in high‐frequency whistles of killer whales may reflect historical geographic isolation between ocean basins and more recent divergence between adjacent populations.